2004
DOI: 10.1097/00001756-200409150-00011
|View full text |Cite
|
Sign up to set email alerts
|

Within- and between-channel gap detection in the human auditory cortex

Abstract: We examined the neural correlates associated with a short gap between two identical pure tones (within-channel) and between two di¡erent tones (between-channel) in an odd-ball paradigm. Gap durations were selected such that a gap between identical tones was as discriminable as a gap between two di¡erent tones. Spatio-temporal dipole source modeling of electrophysiological data revealed a signi¢cant di¡erence between standard and deviant gap stimuli, with mismatch negativity responses that were comparable in am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
2
12

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 24 publications
6
31
2
12
Order By: Relevance
“…The shortest possible wide-spectrum auditory stimulus (like the noise used in this study) is a click, which evokes a single N 1 peak at all intensities. A single-peaked N 1 was also reported in studies on gaps in short (60 ms) tones Heinrich et al, 2004; raw waveforms before derivation of MMN). Taken together, our and earlier findings suggest that the minimum pre-gap sound duration necessary to evoke a two-peaked N-Complex (i.e., the minimum duration of constancy) is just under 500 ms at low intensities, and shorter with higher intensities.…”
Section: The N-complex and The Limits Of Constancymentioning
confidence: 54%
See 4 more Smart Citations
“…The shortest possible wide-spectrum auditory stimulus (like the noise used in this study) is a click, which evokes a single N 1 peak at all intensities. A single-peaked N 1 was also reported in studies on gaps in short (60 ms) tones Heinrich et al, 2004; raw waveforms before derivation of MMN). Taken together, our and earlier findings suggest that the minimum pre-gap sound duration necessary to evoke a two-peaked N-Complex (i.e., the minimum duration of constancy) is just under 500 ms at low intensities, and shorter with higher intensities.…”
Section: The N-complex and The Limits Of Constancymentioning
confidence: 54%
“…In contrast to the double peaked N 1 complex to gaps in continuous noise, two studies on gaps in short (tens of msec) tones Heinrich et al, 2004) have reported a single-peaked N 1 to the gaps. In one of these studies (Heinrich et al, 2004), dipole source estimation suggested that the bilateral generators of the N 1 were in the superior temporal gyrus near the primary auditory cortex, in general agreement with sources of the double-peaked N 1 to gaps in continuous noise (Pratt et al, 2005).…”
Section: N 1 To Speech and Acoustic Temporal Cuesmentioning
confidence: 83%
See 3 more Smart Citations